1995
DOI: 10.3109/02813439508996771
|View full text |Cite
|
Sign up to set email alerts
|

The Finnmark general practitioner hospital study:Patient characteristics, patient flow and alternative care level

Abstract: The GPHs have a pre-hospital "buffer" function by preventing patients with acute symptoms from being unnecessarily admitted to general hospitals through short-term observation stays. A post-hospital function was also demonstrated, since GPHs allow for long-term follow up stays for patients transferred from general hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 2 publications
2
12
0
Order By: Relevance
“…In order to determine whether GP hospitals may indeed provide a viable alternative to conventional care from the patients' perspective, further study is needed with larger patient groups and with more suitable questionnaires. Our data show a number of similarities with some GP hospital surveys from the United Kingdom and Norway (2,6,16). With a focus on observation and low care, the GP hospitals are usually nurse-led, have access to their own diagnostic facilities and to paramedical and specialist care from outpatient clinics in the same hospital location.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In order to determine whether GP hospitals may indeed provide a viable alternative to conventional care from the patients' perspective, further study is needed with larger patient groups and with more suitable questionnaires. Our data show a number of similarities with some GP hospital surveys from the United Kingdom and Norway (2,6,16). With a focus on observation and low care, the GP hospitals are usually nurse-led, have access to their own diagnostic facilities and to paramedical and specialist care from outpatient clinics in the same hospital location.…”
Section: Discussionsupporting
confidence: 57%
“…1. The health-related quality-of-life scores 1 of patients in the three bed categories on admission (GP, RH and NH patients) 2,3 and two reference groups (chronically ill patients and healthy subjects) 4 . 1 For readability, standard deviations (SD) are not represented in this figure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Introduction of a earmarked grant from the Norwegian central government to the municipalities in 2012, aimed at stimulating investments in MAUs, led to a rapid increase in the number of units. By the end of 2014, the first MAUs in the recent wave had been in operation for 2½ years, and just over half of the municipalities, representing 64.8% of the population, were covered by MAUs.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study from Finnmark in north Norway it was estimated that 45% of the patients in the GP hospitals would have been admitted to general hospitals if the GP hospitals had not been available. 1 It was also observed that patients transferred from general hospitals to GP hospitals for follow up care had the longest stays in the GP hospitals. Based on these findings it seems reasonable to anticipate that hospital admission rates are lower and that length of stay are shorter for populations with access to GP hospitals than for those without.…”
mentioning
confidence: 99%